Identifying the effect of tides on groundwater level fluctuations on Gili Ketapang Island, Indonesia - Purnomo, Agung Dwi; Marfai, Muh Aris; Husrin, Semeidi (Journal of Environmental Engineering and Landscape Management, 2021)
This research aims to identify the effect of tides on groundwater level fluctuation in Gili Ketapang Island by using a combination of field monitoring and hydrodynamic modeling. Groundwater data were collected from 5 July to 17 August 2018 from two wells monitoring, while the hydrodynamic model was adopted to identify sea-level conditions. The result explains the sea level around the island is similar among extremely strong correlations between the points. The hydrodynamic model proves a standing wave due to tidal amplification in Madura Strait waters. The effect of tides on the groundwater level characterized by decreasing in amplitudes and time lags as increasing the distance from the coast.